Assessment of the Use of Renewable Energy Sources for the Charging Infrastructure of Electric Vehicles - A. D. Gorbunova; I. A. Anisimov (Ital Publication, 2020)
Application of renewable energy sources is a relevant area of energy supply for urban infrastructure. In 2019, the share of energy produced by such sources reached 11% (for solar energy) and 22% (for wind energy) of the total energy produced during the year. However, these systems require an improvement in their efficiency that can be achieved by introducing electric vehicles. They can accumulate, store and transfer surplus energy to the city’s power grid. A solution to this problem is a smart charging infrastructure. The existing studies in the field of charging infrastructure organization for electric vehicles consider only models locating charging stations in the city or the calculation of their required number. These calculations are based on socio-economic factors and images of a potential owner of an electric vehicle. Therefore, the aim of this study is to develop a methodology for determining the location of charging stations and their required number. The calculation will include the operating features of the existing charging infrastructure, which has not been done before. Thus, the purpose of this article is to research the operation of the existing charging infrastructure. This will provide an opportunity to develop approaches to the energy supply of charging infrastructure and city’s power grid from renewable energy sources. The article presents an analysis of data on the number of charging sessions during the year, month and day. This data enable us to construct curves of the charging session number and suggest ways to conduct the next stages of this study. Doi: 10.28991/esj-2020-01251 Full Text: PDF